Crack-induced response of steel liners in lined rock caverns for underground energy storage - Xinyu Liu; Jianping Yang; Zi-ang Xia; Xiang Ci; Peng Li; Weizhong Chen (Tunnelling and Underground Space Technology, 2027)

Closure of the Eastern Paleo-Asian Ocean: Deformation and geodynamics - Qi’ang Fang; Yongjiang Liu; Qingbin Guan; Zhaoxu Chen; Boran Liu; Sanzhong Li (Gondwana Research, 2026)

Integrating grazing intensity regulation and livestock mobility restoration: A practical test for China’s next-generation rangeland policies - Jianguo Xue; Zunlan Luo; Zhang Chen; Ping Ge; Junchen Lv; Jianhui Huang; Ang Li (Agriculture, Ecosystems & Environment, 2026)

Three-dimensional settling map for intelligent detection of activated sludge (AS) properties and health evaluation of AS based wastewater treatment - Jie Lei; Zhe Liu; Guoning Huang; Jiaxuan Wang; Rushuo Yang; Ying Du; Tianyu Han; Zhuangzhuang Yang; Ang Li; Yongjun Liu; Zhenmin Luo; Rong Chen (Water Research, 2026)

Improving freshwater ecosystem assessment via the integration of eDNA-based multitrophic biotic groups - Minglei Ren; Xue Gong; Mengdie Geng; Ting Hu; Ang Hu; Li Chen; Guangjie Chen; Jianjun Wang (Water Research, 2026)

Synergistic surface engineering enables high-efficiency and stable operation of low-bromine wide-bandgap perovskite solar cells - Zhenzhen Peng; Zhimin Fang; Yi Zhang; Rongyao Lv; Yu-Ang Liu; Dehan Li; Bairu Li; Luozheng Zhang; Shuang Chen; Shangfeng Yang; Jianning Ding (Chemical Engineering Journal, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

MAAI -YOLOv11s: A novel microplastic and nanoplastic particle classification and detection method in microfluidic chip with an improved YOLOv11s model - Kai Zhao; Junzhu Yao; Ang Li; Xuyang Wang; Jingbo Li; Yiyang Huo; Jie Chen; Junsheng Wang (Journal of Water Process Engineering, 2026)

Enhancing power-to-hydrogen efficiency: A streamline-shaped flow channel design for alkaline water electrolyzers verified using a microfluidic experimental platform - Xiudong Duan; Ziyu Liu; Ang Lu; Jiachang Wan; Fan Chen; Desheng Li; Xiaomeng Ai; Chaolong Song; Jiakun Fang (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Interfacial modulation of oil microdroplets via 1O2 stimulated by exposed Fe clusters catalyzing ozonation of 1-adamantanecaboxylic acid for destabilization - Xuan Qu; Qian Xu; Zhiqiang Chen; Ang Li (Water Research, 2026)

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Temperature-sensitive chlorophyll degradation uncouples degreening from other ripening traits and guides postharvest quality improvement in kiwifruit - Ameer Hamza Hafeez; Zheng Zhang; Ang Li; Zhebin Zeng; Yan Chen; Tiantian Li; Xiaomei Ji; Yi Wang; Zhongyan Wang; Yunjiang Cheng; Hamza Sohail; Di Feng; et al. (Postharvest Biology and Technology, 2026)

Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

An integrated optimization framework for voyage and fleet allocation planning in Ro-Ro transport under multiple ship types and contract requirements - Chuanzhong Yin; Xinyi Yao; Luoyi Chen; Lin Li; Zi-Ang Zhang (Ocean Engineering, 2026)

Biodegradation of TDCPP by Chlorella pyrenoidosa: Kinetic, metabolic, and molecular mechanistic insights - Xin Zhang; Yue Chen; Ang Gao; Jinlu Hu; Ke Chen; Haiying Wang (Journal of Hazardous Materials, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

A mimetic drug delivery system using graphene oxide as a component carrier in denitrification: Enhancing long-term stable carbon release and electron transfer capacity of carbon source materials - Ziyi Wang; Yawen Wang; Zhiqiang Chen; Jia Meng; Zhihao Gan; Peng Liu; Ang Li (Chemical Engineering Journal, 2026)

Layer-explicit forest understory measurement: Assessing the capability of UAV LiDAR to extract understory vegetation structure - Zhiyong Qi; Haitao Yang; Zekun Yang; Zitong Bai; Ang Chen; Yixuan Zhang; Yu Ren; Junmin Zhang; Tianyu Xiang; Shiyu Yan; Guangcai Xu; Qinghua Guo (Agricultural and Forest Meteorology, 2026)

Multiscale Characterization of Anhydrous/Hydrous ScCO2 Effects on Coal: Time-Resolved Mineral-Pore Evolution and Divergent Control Mechanisms - Peng Liu; Wanjun Chen; Jingtao Yang; Baisheng Nie; Hengyi He; Hao Xu; Ang Liu (Gas Science and Engineering, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

The synergistic effects of Algal and Bryophyte colonization on soil formation and microbial community assembly in acidic mine tailings - Xinyue Wang; Ang Lv; Yaojia Fu; Zhengyan Wang; Xiangjun Zhou; Lanzhou Chen (Environmental Research, 2026)

Designing hard-soft carbon composite anodes via a normalized pore volume-mass matching strategy for high-performance sodium storage - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Xiaofeng Zhang; Haiyan Liu; Chengwei Fan; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

Transcriptional and functional dissection of cytochrome P450 and ABC transporters underlying tobacco tolerance in Lasioderma serricorne - Junaid Zafar; Shuhao Zhang; Rana Fartab Shoukat; Ling Huang; Ang Li; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Xuewei Zhang; Chen Peng; Shuai Zhong; Xiaoxia Xu; et al. (Journal of Insect Physiology, 2026)

Enhanced treatment of high-algae water and membrane fouling mitigation by SPDA@MIL-101-modified polyethersulfone ultrafiltration membranes with magnetic field regulation and magnetic flocculant assistance - Meng Yao; Ang Li; Zhilin Ran; Xiaoqing Dong; Ruiyan Xiang; Ting Chen; Gang Liu (Journal of Environmental Chemical Engineering, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

MPFT-UNet: A Boundary-Refined and Multi-Scale Dynamic Fusion Network for UAV-Based Port Ship Segmentation - Mengna Shi; Xiulin Qiu; Ang Li; Yuwang Yang; Yaqi Ke; Yilan Chen (Journal of Marine Science and Engineering, 2026)
Ship semantic segmentation based on unmanned aerial vehicle (UAV) imagery has important application value in maritime scenarios such as marine surveillance, port management, and maritime safety. However, UAV images often contain large scale variations of ships, a high proportion of small targets, and complex background interference, including sea surface reflections, waves, and clouds. These factors make accurate segmentation and boundary localization difficult. To address these issues, this paper proposes a UAV-based ship semantic segmentation network, termed MPFT-UNet. The network introduces a Multi-scale Dynamic Sparse Cross-gating (MDSC) module to improve the representation of small targets. A Boundary Supervision Refinement (BSR) module is used to enhance boundary delineation. In addition, a Transformer-based Feature Fusion (FFT) module is applied at the bottleneck layer to strengthen global semantic representation. Experimental results show that MPFT-UNet achieves better performance than existing methods across multiple evaluation metrics. The model obtains an IoU of 0.8365, Dice coefficient of 0.9028, Recall of 0.8881, and AP of 0.95731. These results indicate stable segmentation performance under complex maritime conditions. Compared with the baseline U-Net model, the IoU is improved by approximately 5.1%.

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

Patterns and mechanisms of programmed cell death in bloom-forming Microcystis aeruginosa induced by potent allelochemical juglone - Xu Yang; Jinyuan Chen; Ang Gao; Jinting Li; Yulu Hu; Haiying Wang; Xin Zhang (Journal of Oceanology and Limnology, 2026)

Thiophene-based styrene derivative improves colitis symptoms in DSS-induced BALB/C mice through AhR-mediated gut barrier function and inflammatory responses - Ang-Kun Yang; Yong-Liang Li; Yan-Ying Chen; Yan Liu; Zhi-Yun Du; Chang-Zhi Dong; Bernard Meunier; Hui-Xiong Chen (Toxicology and Applied Pharmacology, 2026)

Chlorine dioxide fumigation induces transcriptomic and metabolomic reprogramming enhancing resistance to soft rot in kiwifruit - Ang Li; Shuang Luo; Di Feng; Xiaoya Chen; Zhidan Zhao; Tiantian Li; Yunhe Meng; Xiaoqin Yang; Yunjiang Cheng; Yunliu Zeng (Postharvest Biology and Technology, 2026)

Contrasting responses to environmental stresses for macroinvertebrates and benthic algae in subtropic Qinhuai rivers - Lei Han; Ming Chen; Song Bai; Ang Hu; Peixuan Zhang; Beryl Ochieng; Yifan Cui; Jinfu Liu; Shaojuan Du; Hao Wu; Xiefa Song; Kang Song; et al. (Journal of Hydrology, 2026)

Temporal dynamics of microbial-soil particulate organic matter in response to nitrogen addition in an alpine steppe - Yilun Hu; Shang Wang; Qiuyu Chen; Ang Hu; Bin Niu; Xiang Chen; Ri Xu; Gengxin Zhang (Applied Soil Ecology, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Metagenomic insights into diet-mediated gut microbial plasticity and functional adaptations in the tobacco beetle Lasioderma serricorne (Coleoptera: Ptinidae) - Junaid Zafar; Shuhao Zhang; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Ang Li; Ling Huang; Xuewei Zhang; Chen Peng; Shuai Zhong; Fengliang Jin; Xiaoxia Xu (Journal of Stored Products Research, 2026)

Design of functional hydrogel beads based on polysaccharide-encapsulated Ganoderma lucidum spores for stability and targeted gastrointestinal delivery of protein–spore complex - Longqin Li; Ang Ma; Jiang Ni; Ruixing Chen; Junzhe Zhang; Zipeng Gong; Hai-Ning Lyu (Carbohydrate Polymers, 2026)

Migration of the post-middle holocene mud depocenter off the Zhejiang coast around 2 ka and its controlling mechanism - Jiandong Qiu; Jian Liu; Rongrong Cheng; Yoshiki Saito; Ang Li; Ke Cao; Yuan Tian; Bin Chen; Zhe Xu; Meina Li (Geo-Marine Letters, 2026)

Dissolved Organic Carbon Shapes Sediment Bacterial Diversity in Continental Lakes - Yarui Chen; Ang Hu; Jianjun Wang (Molecular Ecology, 2026)
Biodiversity patterns such as the latitudinal diversity gradient (LDG) are central to ecology. Compared to macroorganisms, microbial diversity patterns and their underlying mechanisms, particularly in freshwater systems, are understudied despite their importance to ecosystem functioning. Here, we conducted a large‐scale investigation of sediment bacterial communities in China's lakes across a latitudinal gradient from 18°N to 50°N and assessed their diversity patterns, life history strategies, and co‐occurrence networks. Bacterial alpha diversity showed nonsignificant latitudinal pattern, but the community composition exhibited a significant distance‐decay relationship. Climate factors, including mean annual temperature, were not correlated with alpha diversity, which is inconsistent with the “Red Queen” hypothesis. Instead, carbon resources indicated by the absorption coefficients at 254 nm and humification index of dissolved organic matter were positively associated with alpha diversity, supporting the “Resource Partitioning” hypothesis. The quality and quantity of dissolved organic matter also influenced life history traits (e.g., rrn copy number, oligotrophic‐copiotrophic ratios) and co‐occurrence network properties, with increasing refractory carbon decreasing the ratio of negative to positive network cohesion. Dissolved organic matter influenced bacterial diversity primarily through its indirect effects on life history strategies and potential biotic interactions revealed by structural equation modeling. Our findings highlight the dominant role of carbon resources over climate in structuring sediment bacterial diversity in freshwater ecosystems.

CFD Numerical Simulation Study on Hydrogen Fuel Combustion and Emission Characteristics of Marine Two-Stroke Low-Speed Engines - Zhizheng Wang; Hao Guo; Ang Sun; Song Zhou; Jialu Song; Yi Chai; Yue Chen (Journal of Marine Science and Engineering, 2026)
To meet the global climate change challenge and the International Maritime Organization’s (IMO) greenhouse gas emission reduction strategy, and promote the shipping industry’s transition to clean energy, this study focuses on the 6S35 2-stroke marine low-speed engine to explore hydrogen fuel combustion and emissions in the cylinder. A detailed chemical reaction kinetics model is constructed on the CONVERGE platform, coupling 42 components and 168 elementary reactions, integrating the SAGE combustion model with the extended Zeldovich NOx mechanism for refined numerical simulation of hydrogen combustion. Model validation shows the cylinder pressure peak simulation error is within 5%. Research results indicate hydrogen fuel has significant premixed combustion characteristics with a violent and concentrated heat release. Under simulation, the cylinder explosion pressure reaches about 28 MPa, and the max combustion temperature nears 3000 K, far exceeding traditional diesel engines. In terms of emissions, hydrogen’s carbon-free characteristic keeps CO2 and CO emissions at extremely low levels (concentrations of approximately 0.02 and 0.085, respectively); whereas NOx emissions exhibit strong “high temperature dependence” and “expansion cooling effect,” with peak concentrations approaching 0.00042. This numerical model can effectively predict the combustion performance of hydrogen fuel, potentially providing a reference for optimizing fuel injection strategies and combustion chamber design to achieve efficient and clean combustion, and offering a theoretical basis for the development and commercial application of marine hydrogen fuel engines.

Corrigendum to “The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review” [Sci. Total Environ. 927 (2024), 172169] - Kejun Liao; Chaoqi Chen; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2026)

Cold-summer and summer-snowfall trends and their impacts on vegetation in a warming Mongolian Plateau - Zhang Chen; Junchen Lv; Hao Jiang; Dongyang Lei; Jianguo Xue; Ang Li; Jianhui Huang (Journal of Arid Environments, 2026)

Incorporating localized weather station data for microclimate-integrated urban building energy modeling: A campus-scale decarbonization study - Xueyu Chen; Tao Wang; Nyuk Hien Wong; Yu Qian Ang (Building and Environment, 2026)

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

Isolation, characterization, and anti-neuroinflammatory activity of sesquiterpenoids from Pogostemon esquirolii - Yebi Qin; Xinyan Shao; Yinzheng Xie; Hailin Lu; Kaien Chen; Xi Zheng; Guodong Chen; Lishe Gan; Song Ang; Dongli Li (Phytochemistry, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

Effects of curcumin and Curcuma longa extract on inflammatory biomarkers in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE): a systematic review and meta-analysis of randomized controlled trials - Ang-Jun Liu; Po-Chang Wu; Yu-Pei Chen; Hsueh-Ting Chu; Hen-Hong Chang (Inflammation Research, 2025)

Determinants of bovine brucellosis across herds and individuals: A Bayesian meta-analysis - Zihan Tian; Yingying Dong; Cairen Ga; Qiuzhong Suo Nan; Qiuzang Suo Ang; Qiumei Shi; Aizhen Guo; Yingyu Chen (The Veterinary Journal, 2025)

ALM-LED: autonomous LiDAR mapping in underground space with Luojia explorer anti-collision drone - Shangzhe Sun; Chi Chen; Bisheng Yang; Yuhang Xu; Leyi Zhao; Yong He; Ang Jin; Liuchun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Synergistic lipid-lowering effects of Monascus purpureus and honeysuckle co-fermentation products: Insights from metabolomics, network pharmacology, and cellular experiments - Arzugul Ablimit; Qing Sun; Mengxue Chen; Huijun Dong; Wenbo Liu; Yike Zhai; Duchen Zhai; Ang Huang; Dingrong Kang; Baoguo Sun; Chengtao Wang; Chan Zhang (Food Bioscience, 2025)

Boosting the plateau capacity via phosphoric acid cross-linking strategy for phenolic resin-based hard carbon - Xiaoqi Yu; Xiaoyu Xu; Hanyu Wei; Haiyan Liu; Ang Li; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Biochar-mediated electron transfer in a spinel ferrite catalyst boosts peracetic acid activation for water decontamination - Lu Xia; Xinlan Li; Zhuojun Wei; Ang Liu; Jianqiu Chen; Jingge Shang (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

Molecular Properties of Dissolved Organic Matter across Earth Systems: A Meta-Analysis - Lei Han; Ang Hu; Hellen Lucas Mzuka; Xingting Chen; Ji Shen; Jianjun Wang (Journal of Earth Science, 2025)

Application and challenges of machine learning in microbial remediation: A review of current status and future directions - Yueyan Zhang; Jun Sasaki; Ang Li; Jundong Chen (Critical Reviews in Environmental Science and Technology, 2025)

Impact of Fluid Sloshing on BOG Generation in Type B LNG Tanks During Ship Emergency Stops - Haikang Zhao; Gang Wu; Jiachen Chen; Xigang Pu; Sicong Wang; Yuhao Yuan; Ang Sun (Journal of Marine Science and Engineering, 2025)
The safe and efficient transport of Liquefied Natural Gas (LNG) is critically dependent on understanding fluid dynamics within cargo tanks, which directly influence structural integrity and operational safety. Study employs the Volume of Fluid (VOF) method to simulate fluid sloshing and phase change dynamics in Type B LNG cargo tanks during emergency stop conditions. The transient simulations employ a time step of 5 × 10−3 s, a model with 46,840 grids, and the analysis focuses on impact forces on tank walls, their dependence on filling levels. Results show that the flow disturbance caused by vessel rolling increases BOG generation fluctuations by approximately 35%. Sloshing significantly increases BOG generation, particularly after a 10 s relaxation period, as the initial shock enhances heat transfer and mixing, accelerating vapor production. Original components of LNG are sensitive to BOG generation and impact forces on the front bulkhead are significantly higher than on the rear, with peak impacts occurring. The filling rate is a critical parameter influencing fluid dynamics and safety in LNG transportation. Impact magnitude increases with fill level up while at about 80% it declines; impact timing shortens at higher fill ratios. A BOG generation mechanism in which microscale turbulence and ongoing thermal imbalance govern the kinetics of evaporation phase transitions was proposed. It was discovered that the impact forces and BOG production exhibit rise–fall–rise patterns driven by impact dynamics, condensation, and evaporation processes. The findings highlight the critical role of fluid sloshing in affecting tank safety and operational efficiency, offering insights into designing more resilient LNG cargo tanks and optimizing transportation safety and economy.

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Straightened velocity obstacle algorithm for inland ships collision avoidance - Zhi'ang Wang; Yamin Huang; Linying Chen; Liang Huang; Yuanqiao Wen (Ocean Engineering, 2025)

Effects of Per- and polyfluoroalkyl substances on atherosclerosis: an evidence-based risk assessment in the context of the TRAEC strategy - Yiming Zhu; Zhenzhen Tan; Ziwen An; Longfei Li; Mingmei Guo; Wenjing Duan; Zhixia Yu; Ziang Chen; Yi Liu; Ang Li; Huicai Guo (Environmental Research, 2025)

Weathering modulates soil microbial biodiversity in a Sygera Mountain alpine forest, Tibetan Plateau - Hongzhe Jiao; Qiuyu Chen; Bin Niu; Xiaoqin Yang; Guiyao Zhou; Ang Hu; Jian Wang; Guicai Si; Jiangrong Li; Eryuan Liang; Manuel Delgado-Baquerizo; Gengxin Zhang (Applied Soil Ecology, 2025)

Scale-factor-based regional zenith tropospheric delay modeling for real-time precise point positioning - Hao Chen; Ningbo Wang; Zishen Li; Kefei Zhang; Suqin Wu; Peng Sun; Ang Liu; Gongwei Xiao (Advances in Space Research, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Experimental investigation on wave attenuation capacity of kelp farms - Yushun Lian; Jiantao Ma; Dong-ang Li; Jinhai Zheng; Aifeng Tao; Wenxing Chen; Jisheng Zhang; Solomon C. Yim (Ocean Engineering, 2025)

Estimating rainfall intensity from surveillance audio: A hybrid model-data-driven framework - Xing Wang; Kun Zhao; Haiqin Chen; Ang Zhou; Jiuwei Zhao; Shuaiyi Shi; Thomas Glade (Journal of Hydrology, 2025)

Pediatric inflammatory bowel disease in mother-child pairs: clinical risk factors and gut microbiota characteristics - Cunzheng Zhang; Ruqiao Duan; Nini Dai; Yuzhu Chen; Gaonan Li; Xiao’ang Li; Xiaolin Ji; Xuemei Zhong; Zailing Li; Liping Duan (Journal of Zhejiang University-SCIENCE B, 2025)

Morphological characteristics and evolution of stream potholes in the Quanfengtan reach of the Lower Zijiang River, Hunan Province, China - Linhong Chen; Fenliang Liu; Nan Ding; Junhua Huang; Yu’ang Liu; Hongshan Gao (Journal of Mountain Science, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Synergistic experimental-numerical investigation of performance optimization and dynamic behavior in perforated electrode electrocoagulation systems for emulsified oil wastewater remediation - Ang Li; Bing Wang; Meng Yao; Zhilin Ran; Zheng Ju; Ting Chen (Process Safety and Environmental Protection, 2025)

Recent advances of constructed wetlands utilization under cold environment: Strategies and measures - Kaiyue Hao; Yaqian Zhao; Ting Wei; Du Wen; Ang Liu; Yulong Huang; Zhenzhen Chen (Process Safety and Environmental Protection, 2025)

Impact of C-8 hydroxylation and C-7 methylglucosylation of dihydroquercetin on glucose metabolism in diabetic zebrafish larvae - Yong Cheng; Beijun Ang; Dandan Ma; Zhiwei Li; Fengxian Guo; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Jie Chen; Benu Adhikari; Liduan Yin; Tong Wang; et al. (Food Bioscience, 2025)

Quantifying graphitic curvature and engineering closed pores in phenolic resin hard carbons for enhanced plateau capacity in sodium-ion batteries - Xiaotian Li; Jiapeng Zhang; Renlu Yuan; Boyang Zhao; Chuang Qiu; Dengke Wang; Man Yuan; Ang Li; Haiyan Liu; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Two new alkamides and a new polyacetylene glucoside from Achillea alpina L. - Ang Li; Xiu-Wei Li; Huan Guo; Qiang Guo; Xia Wu; Xiao-Qing Chen (Phytochemistry Letters, 2025)

Nickel-doped ZIF-L as a high-performance catalyst for peroxymonosulfate activation and singlet oxygen-mediated As(III) removal - Jian Ye; Chuang Li; Zhiming Yang; Xuan Hu; Qiang Chen; Ang Sun; Mingyang Dai; Shaobo Liu; Chunping Yang (Journal of Environmental Chemical Engineering, 2025)

Students’ thermal comfort and cognitive performance in tropical climates: A comparative study - Chao Cen; Erna Tan; Selvam Valliappan; Edward Ang; Zhimin Chen; Nyuk Hien Wong (Energy and Buildings, 2025)

Sulfur-bonded hard carbon with enhanced interfacial and bulk kinetics for potassium-ion hybrid capacitors - Chuang Qiu; Anuj Kumar; Mohammad Tabish; Xinzhuo Mai; Liewen Guo; Ying Zhao; Yibo Zhu; Ang Li; Ghulam Yasin; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

A Circular Economy Model of Sustainable Growth - Jhy -Yuan Shieh; Brian Chi-ang Lin; Jhy-Hwa Chen (Circular Economy and Sustainability, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Changes in grassland types caused by climate change and anthropogenic activities have increased carbon storage in alpine grassland ecosystem - Min Zhang; Ang Chen; Xiaoyu Xing; Dong Yang; Zichao Wang; Xiuchun Yang (Global and Planetary Change, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Multiplex quantitative PCR assay for porcine circoviruses 2 and 3 and its application for measuring infection rates at different stages of pig production - Zhen Li; Shuaiyin Guan; Jiaying Zhao; Yuhuan Chen; Yang Han; Ang Tian; Saisai Zhou; Huanchun Chen; Yunfeng Song (Archives of Virology, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Study on short-term total hardness prediction of water quality based on CNN-BiLSTM-SA model: A case study of Henan Province - Huan Xu; Hehu Zhang; Youwei Wang; Lingling Lu; Ang Wu; Ying Chen; Yahui Li; Chuanxin Dong; Xiushan Wang (Journal of Water Process Engineering, 2025)

Characterization of two pectic polysaccharides from Rosa roxburghii Tratt fruit and their protection on Bifidobacterium against antibiotic damage - Ting-Ting Tu; Xiao-Hui Yuan; Yu-Heng Mao; Yan-Chun Wang; Zheng-Hao Chen; Lei Wang; You Luo; Chun-Xiao Wang; Shu-Yi Qiu; Ang-Xin Song (Food Bioscience, 2025)

Molecular detection and genotyping of bovine viral diarrhea virus in four provinces of China - Ying Liu; Feng Zhou; Xuan-ang Wang; Xi-Meng Chen; Lan-Lan Zheng; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Clonidine Ameliorates Neuroinflammation in the Rat Model of Tourette Syndrome - Zhongling Ke; Yuxian Huang; Ang Wang; Yanhui Chen (Journal of Neuroimmune Pharmacology, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

Spatial configuration engineering of phenolic resins to tune the closed pores of hard carbon for enhanced plateau-capacity sodium storage - Liewen Guo; Chuang Qiu; Haiyan Liu; Renlu Yuan; Xiaotian Li; Xin Li; Kairan Li; Wanxiong Zhu; Mohammad Tabish; Xuewei Liu; Ang Li; Xiaohong Chen; et al. (Chemical Engineering Journal, 2025)

Study on the genesis of carbonate cements in tight and non-tight sandstone reservoirs in Fukang Sag - Li Na; Wang Zi'ang; Liu Gang; Wang Guozhi; Huang Sheng; Liu Jinlong; Jing Yang; Chen Haixia (Ore and Energy Resource Geology, 2025)

Unveiling the rise of microalgae-based foods in the global market: Perspective views and way forward - Wei Shan Ang; Phei Er Kee; John Chi-Wei Lan; Wei-Hsin Chen; Jo-Shu Chang; Kuan Shiong Khoo (Food Bioscience, 2025)

Hydroxylation of dihydromyricetin via Beauveria bassiana fermentation enhances its efficacy in improving insulin signaling: Insights into inflammation, oxidative stress, and endoplasmic reticulum stress - Yong Cheng; Junhao Wu; Yueqing Gao; Beijun Ang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Jie Chen; Zhiyong He; Fengfeng Wu (Food Research International, 2025)

Development of red grapefruit jam fermented with Monascus purpureus: Effect of naringenin on Monascus purpureus growth and metabolism - Chan Zhang; Congcong Wang; Arzugul Ablimit; Mengxue Chen; Qing Sun; Huijun Dong; Wenbo Liu; Ang Huang; Bobo Zhang; Wenlin Hu; Chengjian Liu; Chengtao Wang (Food Bioscience, 2025)

Estimation of crude protein content in natural pasture grass using unmanned aerial vehicle hyperspectral data - Huimin Qi; Ang Chen; Xiuchun Yang; Xiaoyu Xing (Computers and Electronics in Agriculture, 2025)

Polylactic acid microplastics induced negative priming and improved carbon sequestration via microbial processes in different paddy soils - Liying Chen; Lanfang Han; Fayuan Wang; Qi'ang Chen; Hongkai Huang; Jie Wang; Chuanxin Ma; Ke Sun; Matthias C. Rillig; Yakov Kuzyakov; Zhifeng Yang (Soil Biology and Biochemistry, 2025)

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Unveiling fundamental first-principles insights into single-atom transition metal photocatalysts for carbon dioxide reduction - Chen-Chen Er; Lutfi K. Putri; Yee Sin Ang; Siang-Piao Chai (Fuel, 2025)

Salinity tolerance assessment of different families of the razor clam Sinonovacula constricta using physiological traits - Chen Yihua; Shao Zhengyu; Zhou Guolong; Hu Ang; Ding Hongbing; Li Haoyu; Dong Zhiguo; Niu Donghong; Li Jiale (Aquaculture, 2025)

Enhancing fish sludge bioconversion kinetics for nutrient recovery in aquaponics using a modified biological aerated filter with a novel media of polyhedral hollow spheres - Ang Chen; Hong Zhang; Yongxia Zi; Yueshu Gao; Chew Tin Lee; Chunjie Li (Journal of Environmental Management, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Delving into South China Sea microplastic pollution: Abundance, composition, and environmental risk - Jiehong He; Xiaoyu Guo; Xuanwei Zhang; Qi-ang Chen; Kuo Gao; Lanfang Han; Chao Xu (Marine Pollution Bulletin, 2024)

Endophytic bacteria in Halogeton glomeratus from mining areas are mainly Sphingomonas pseudosanguinis, with a Cyanobacteria moving from roots to leaves to avoid heavy metals - Xisheng Tai; Ruiqi Yang; Jun Li; Ang Li; Wei Chen; Jiajia Ding (Rhizosphere, 2024)

Salinity impacts on n-alkanes in lake sediments of the Badain Jaran Desert, Northwestern China: Implications for paleoclimate reconstruction - Meng Li; Zhuolun Li; Shipei Dong; Lin Chen; Xianbao Su; Chen'ao Lu; Aifeng Zhou; Nai'ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Response and adaptation of Chlorella pyrenoidosa to 6PPD: Physiological and genetic mechanisms - Yue Chen; Lei Yuan; Jinyuan Chen; Ang Gao; Jinlu Hu; Haiying Wang; Xin Zhang (Journal of Hazardous Materials, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Bio-based microplastic polylactic acid exerts the similar toxic effects to traditional petroleum-based microplastic polystyrene in mussels - Zhen Zhong; Wenrui Shang; Peiwen Yang; Shixiu Wang; Liming Chen; Zhaowen Chen; Li’ang Li; Muhammad Faisal Khalil; Menghong Hu; Xiangrong Xu; Youji Wang (Science of The Total Environment, 2024)

Behavior of surface loaded clay foundation reinforced by GESCs with lateral geosynthetic cushion under freeze-thaw cycles - Zi-Ang Gu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Review on recent advances in supported metal catalysts for synthesis of high energy density fuels - Tian Li; Dandan Jia; Shenglan Zhou; Zhiyuan Liu; Juan Chen; Tao Ban; Ang Li; Haijian Li; Hongyi Gao (Fuel, 2024)

Tris(1-chloro-2-propyl) phosphate enhances the adverse effects of biodegradable polylactic acid microplastics on the mussel Mytilus coruscus - Zhen Zhong; Wei Huang; Yiwei Yin; Shixiu Wang; Liming Chen; Zhaowen Chen; Jiacheng Wang; Li'ang Li; Mansoor Khalid; Menghong Hu; Youji Wang (Environmental Pollution, 2024)

Regulation of thermal migration channel in cellulose hydrogel to enhance thermopower - Xinyuan Cheng; Yang Hu; Pan Chen; Haisong Qi; Ang Lu (Chemical Engineering Journal, 2024)

Janus-structured colorimetric and fluorescent nanocomposites with highly luminescent retention to enhance point-of-care diagnosis - Xuan-ang Shen; Xirui Chen; Haoxiang Zhou; Song Chen; Jinyu Wu; Xiangmin Li; Xiaolin Huang; Yonghua Xiong (Chemical Engineering Journal, 2024)

Was there an active continental margin arc along the western margin of Zhangguangcailing Terrane in the eastern Central Asian Orogenic Belt? - Zhaoxu Chen; Boran Liu; Qingbin Guan; Yongjiang Liu; A.Yu. Peskov; Sanzhong Li; Qi’ang Fang (Lithos, 2024)

Stretchable, adhesive, conductive hydrogel initiated by liquid metal complex for multi-functional sensing - Yuecong Luo; Qiannian Yang; Minzhang Chen; Kaixiang Long; Cuicui Su; Jingxing Li; Mingkun Huang; Ang Lu; Shishang Guo (Chemical Engineering Journal, 2024)

Research on fine modeling of dispersion fuel plate based on lattice method - Yuqing Chen; Pengfei Liu; Song Li; Lei Lou; Ang Li (Annals of Nuclear Energy, 2024)

Identifying climate refugia for wild yaks (Bos mutus) on the Tibetan Plateau - Hang Zhao; Hongyi Cheng; Nai'ang Wang; Liqiong Bai; Xiaowen Chen; Xiao Liu; Bin Qiao (Journal of Environmental Management, 2024)

Behavior of geosynthetic-encased stone column reinforced foundation under freeze-thaw cycles - Zi-Ang Gu; Chungsik Yoo; Jian-Feng Chen (Geotextiles and Geomembranes, 2024)

Experimental observation of exceptional bound states in a classical circuit network - Deyuan Zou; Tian Chen; Haiyu Meng; Yee Sin Ang; Xiangdong Zhang; Ching Hua Lee (Science Bulletin, 2024)

A CNN-SVR model for NO2 profile prediction based on MAX-DOAS observations: The influence of Chinese New Year overlapping the 2020 COVID-19 lockdown on vertical distributions of tropospheric NO2 in Nanjing, China - Xin Tian; Zijie Wang; Pinhua Xie; Jin Xu; Ang Li; Yifeng Pan; Feng Hu; Zhaokun Hu; Mingsheng Chen; Jiangyi Zheng (Journal of Environmental Sciences, 2024)

Aggregation-induced emission nanoparticles facilitating multicolor lateral flow immunoassay for rapid and simultaneous detection of aflatoxin B1 and zearalenone - Yi Zhang; Guoxin Chen; Xirui Chen; Xiaxia Wei; Xuan-ang Shen; Hu Jiang; Xiaoyang Li; Yonghua Xiong; Xiaolin Huang (Food Chemistry, 2024)

Sustainable reprocessing of lithium iron phosphate batteries: A recovery approach using liquid-phase method at reduced temperature - Tingyan Ren; Bolin Zou; Bin Cai; Tong Liang; Junhao Chen; Rui Huang; Dahai Yang; Hongfa Xiang; Edison Huixiang Ang; Xiaohui Song (Waste Management, 2024)

The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review - Kejun Liao; Chaoqi Chen; Wenyan Ye; Jing Zhu; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2024)

Non-destructive prediction of ready-to-eat kiwifruit firmness based on Fourier transform near-infrared spectroscopy - Gang Ding; Ke Jin; Xiaoya Chen; Ang Li; Zhiqiang Guo; Yunliu Zeng (Postharvest Biology and Technology, 2024)

Bioinspired wet adhesive carboxymethyl cellulose-based hydrogel with rapid shape adaptability and antioxidant activity for diabetic wound repair - Hongxia Xie; Ge Shi; Ruizi Wang; Xueyu Jiang; Qianqian Chen; Aixi Yu; Ang Lu (Carbohydrate Polymers, 2024)

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Carbon sequestration potential of biochar in soil from the perspective of organic carbon structural modification - Lanfang Han; Cuiling Lu; Liying Chen; Fayuan Wang; Qi’ang Chen; Kuo Gao; Yuanyuan Yu; Chao Xu (Applied Soil Ecology, 2024)

LncRNA RPLP0P2 Promotes Colorectal Cancer Proliferation and Invasion via the miR-129-5p/Zinc Finger and BTB Domain-Containing 20 Axis - Hang Yuan; Peng Yu; Zi-Ang Wan; Bing-Chen Chen; Shi-Liang Tu (Biochemical Genetics, 2024)

Revolutionary MOF-enhanced anion exchange membrane for precise monovalent anion separation through structural optimization and doping - Junhua Li; Zhipeng Xu; Junbin Liao; Edison Huixiang Ang; Xuanhua Chen; Junjie Mu; Jiangnan Shen (Desalination, 2024)

Disinfection by-products control in wastewater effluents treated with ozone and biological activated carbon followed by UV/Chlor(am)ine processes - Yu Zhong; Yiwei Chen; Say Leong Ong; Jiangyong Hu; Viswanath Balakrishnan; Wui Seng Ang (Science of The Total Environment, 2024)

Cross-scale mapping of above-ground biomass and shrub dominance by integrating UAV and satellite data in temperate grassland - Ang Chen; Cong Xu; Min Zhang; Jian Guo; Xiaoyu Xing; Dong Yang; Bin Xu; Xiuchun Yang (Remote Sensing of Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Dynamic monitoring of aboveground biomass in inner Mongolia grasslands over the past 23 Years using GEE and analysis of its driving forces - Dong Yang; Zhiyuan Yang; Qingke Wen; Leichao Ma; Jian Guo; Ang Chen; Min Zhang; Xiaoyu Xing; Yixin Yuan; Xinyu Lan; Xiuchun Yang (Journal of Environmental Management, 2024)

Role of inflammatory lipid and fatty acid metabolic abnormalities induced by plastic additives exposure in childhood asthma - Zhiyu Chen; Fang Li; Lei Fu; Yu Xia; Ying Luo; Ang Guo; Xiaona Zhu; Huifang Zhong; Qian Luo (Journal of Environmental Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Transformation mechanisms of ammonium and nitrate in subsurface wastewater infiltration system: Implication for reducing greenhouse gas emissions - Xulun Zhou; Haibo Li; Ang Wang; Geshere Abdisa Gurmesa; Xueyan Wang; Xi Chen; Chenxi Zhang; Yunting Fang (Water Research, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Early Paleozoic tectonic affinity of the Lesser Xing'an–Zhangguangcai Range, NE China: A continental arc along the western margin of the Jiamusi Block - Qingbin Guan; Boran Liu; Zhaoxu Chen; Yongjiang Liu; Sanzhong Li; Qi'ang Fang; Yujia Du (Lithos, 2024)

Study on the degradation of triethylamine wastewater by catalytic ozone-biological coupled system of Ce-Fe@ZSM-5 - Xiangyu Xiao; Zhenqi Zhou; Zhongqin Jiang; Chunlin Jiao; Yinna Liang; Ang Du; Yuxuan Cai; Jianhua Xiong; Yongli Chen (Journal of Water Process Engineering, 2024)

Mussel-inspired modification of 2D MoS2 to construct a hybrid nanocomposite membrane with enhanced pervaporation dehydration of isopropanol - Marwin R. Gallardo; Jyun-Xiang Ciou; Chen-Hsiu Wang; Micah Belle Marie Yap Ang; Jeremiah C. Millare; Chi-Lan Li; Hui-An Tsai; Shu-Hsien Huang; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2024)

Design and fabrication of self-suspending aluminum-plastic/semiconductor photocatalyst devices for solar energy conversion - Zhi-Ang Zhao; Jingyun Mao; Chengjing Lu; Shuangqiao Yang; Qingrong Qian; Qinghua Chen; Hun Xue; Xiaoli Sun; Min-Quan Yang (Journal of Environmental Sciences, 2024)

Centrifuge investigation on behavior of geosynthetic-encased stone column supported embankment under freeze-thaw cycles - Zi-Ang Gu; Fu-Jun Niu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Eco-infused interfacial enhancement of the anti-biofouling activity in anion exchange membranes for electrodialysis desalination - Yuyang Yao; Yueyue Lu; Yuan Li; Yanjing Ma; Edison Huixiang Ang; Jingwen Xu; Heda Ding; Yuna Shi; Yitao Chen; Junbin Liao; Zhenlu Shen; Jiangnan Shen (Chemical Engineering Journal, 2024)

Application of solid electrolytes in electrochemical reduction of CO2 or O2 - Jiayue Li; Zhuowen Wang; Sibei Liu; Zhonglin Chen; Jixian Yang; Zhiqiang Chen; Ang Li; Qinxue Wen; Li Wang; Shan Qiu; Chongwei Cui; Huiyuan Deng; et al. (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Insights into the fermentation potential of pollen: Manufacturing, composition, health benefits, and applications in food production - Yong Cheng; Beijun Ang; Chaoyi Xue; Zhenyu Wang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Wei Zhang; Jie Chen; Zhiyong He (Trends in Food Science & Technology, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

Performance of fish sludge solubilization and phototrophic bioconversion by purple phototrophic bacteria for nutrient recovery in aquaponic system - Tian Xia; Ang Chen; Yongxia Zi; Yuan Zhang; Qianzhi Xu; Yueshu Gao; Chunjie Li (Waste Management, 2023)

Multi-omics analyses reveal relationships among polyphenol-rich oolong tea consumption, gut microbiota, and metabolic profile: A pilot study - Ang Li; Ruixin Kou; Haiwei Liu; Mengshan Chen; Jin Wang; Qisijing Liu; Xiaolong Xing; Bowei Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Carbon-based hierarchical porous structure accelerates heterogeneous nucleation of PEG molecules for solar/electro-driven thermal energy storage - Ruze Liu; Ang Li; Jinyan Liu; Wengeng Liu; Hao Zheng; Qingyang Du; Xiao Chen; Cheng Dong (Chemical Engineering Journal, 2023)

Three birds, one-stone strategy for synthesis of hierarchically arrayed defective MnCo2O4@NF catalyst for photothermal preferential oxidation of CO in H2-rich streams - Ang Zhou; Xiaolin Guo; Siyi Zhong; Zi'ang Chen; Qiaoling Kang; Miaogen Chen; Dingfeng Jin; Meiqiang Fan; Renxian Zhou; Tingli Ma (Chemical Engineering Journal, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Boosting photocatalytic activity of CdLa2S4/ZnIn2S4 S-scheme heterojunctions with spatial separation of photoexcited carries - Meng Dai; Huijun Yu; Wenhan Chen; Kongyu-Ang Qu; Dong Zhai; Chengcheng Liu; Shan Zhao; Shuguang Wang; Zuoli He (Chemical Engineering Journal, 2023)

Correction to: Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Combined toxic effects of nanoplastics and norfloxacin on mussel: Leveraging biochemical parameters and gut microbiota - Ran Xu; Li'ang Li; Jiahui Zheng; Chenglong Ji; Huifeng Wu; Xiang Chen; Yuchuan Chen; Menghong Hu; Elvis Genbo Xu; Youji Wang (Science of The Total Environment, 2023)

Investigation of dynamic crack formation mechanism based on a new crack dynamic driving model - Xiao Liu; Peng Yan; Wenbo Lu; Jin Zhu; Xiangyu Zhang; Ang Lu; Ming Chen; Gaohui Wang (Computers and Geotechnics, 2023)

The thermodynamics of enhanced dope stability of cellulose solution in NaOH solution by urea - Yu Chen; Yoshiharu Nishiyama; Ang Lu; Yan Fang; Ziqiang Shao; Tao Hu; Dongdong Ye; Haisong Qi; Xiaodong Li; Jakob Wohlert; Pan Chen (Carbohydrate Polymers, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

Atomic defects engineering on Fe-N4 sites for boosting oxygen reduction by in-situ ZnO thermal etching strategy - Shengjie Wei; Lei Li; Ang Li; Lei Zhang; Haibo Hu; Dawei Pang; Qinghua Zhang; Hai Xiao; Wenxing Chen (Chemical Engineering Journal, 2023)

Re-Exploring the Inflammation-Related Core Genes and Modules in Cerebral Ischemia - Wenjing Lv; Junqi Jiang; Yi Xu; Zhiyuan Chen; Zixuan Wang; Ang Xing; Xueping Zheng; Tingting Qu; Qi Wan (Molecular Neurobiology, 2023)

Differential physiological response of marine and freshwater microalgae to polystyrene microplastics - Hengtao Xu; Li’ang Li; Youji Wang; Kecheng Qiu; Siyang Chen; Jiangning Zeng; Ruijuan Liu; Qikun Yang; Wei Huang (Journal of Hazardous Materials, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Characteristics and transfer paths of CO2 emissions embodied in trade and China’s carbon reduction strategies - Jingjing Chen; Xinru Lin; Xiaojun Wang; Lihong Peng; Ang Yu (Environmental Science and Pollution Research, 2023)

Dual RNA-seq reveals a host-pathogen interaction transcriptional regulation pattern between Cryptocaryon irritans and large yellow croaker (Larimichthys crocea) - Yulin Bai; Yue Liu; Ang Qu; Jiaying Wang; Ji Zhao; Qiaozhen Ke; Xintong Chen; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Aquaculture, 2023)

PFAS-induced lipidomic dysregulations and their associations with developmental toxicity in zebrafish embryos - Zhiyi Yang; Lei Fu; Mengxi Cao; Fang Li; Jingguang Li; Zhiyu Chen; Ang Guo; Huifang Zhong; Wenbo Li; Yong Liang; Qian Luo (Science of The Total Environment, 2023)

Palaeoenvironmental evolution of the Badain Jaran Desert hinterland during the Early to Middle Holocene: A multi-proxy reconstruction on Taoerlegetu paleolake, northwest China - Chen’ao Lu; Nai'’ang Wang; Lvlv Zhang; Zhuolun Li; Wenwei Zhao; Meng Li; Xianbao Su; Yixin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Spatiotemporal variations of precipitation concentration influenced by large-scale climatic factors and potential links to flood-drought events across China 1958–2019 - Sijia Fu; Huilan Zhang; Qiang Zhong; Qigang Chen; Ang Liu; Jun Yang; Jianzhuang Pang (Atmospheric Research, 2023)

Identification and Expression Analysis of LncRNAs Reveal the Immune Mechanism of Visceral White-Nodules Disease Resistance in Large Yellow Croaker - Yulin Bai; Xintong Chen; Ang Qu; Yue Liu; Ji Zhao; Qiaozhen Ke; Fei Pu; Linni Wu; Hongshu Chi; Hui Gong; Tao Zhou; Peng Xu (Marine Biotechnology, 2023)

Green development strategy of offshore wind farm in China guided by life cycle assessment - Jingjing Chen; Bingjing Mao; Yufeng Wu; Dongya Zhang; Yiqun Wei; Ang Yu; Lihong Peng (Resources, Conservation and Recycling, 2023)

Response of ecosystem services in Beijing-Tianjin Sandstorm Source Control Project to differing engineering measures scenarios - Xiaoyu Xing; Xiuchun Yang; Jian Guo; Ang Chen; Min Zhang; Dong Yang; Zhiyan Hou; Huilong Zhang; Xing Wang (Journal of Cleaner Production, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

Polycyclic aromatic hydrocarbons (PAHs) in the upstream rivers of Taihu Lake Basin, China: spatial distribution, sources and environmental risk - Lingling Wang; Xiaoming Ren; Xiaoping Wang; Perran Ye; Fei Wang; Jiade Cheng; Yan Chen; Ang Yu; Limin Zhang; Yang Qiu (Environmental Science and Pollution Research, 2022)

Improved Agrobacterium tumefaciens-mediated transformation using antibiotics and acetosyringone selection in cucumber - Changxia Du; Li’ang Chai; Chen Liu; Yuyang Si; Huaifu Fan (Plant Biotechnology Reports, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Iron-withdrawing anti-infectives for new host-directed therapies based on iron dependence, the Achilles’ heel of antibiotic-resistant microbes - Bruce E. Holbein; M. Trisha C. Ang; David S. Allan; Wangxue Chen; Christian Lehmann (Environmental Chemistry Letters, 2021)

Experimental investigation of temperature distribution and spontaneous combustion tendency of coal gangue stockpiles in storage - Ang Li; Changkun Chen; Jie Chen; Peng Lei; Yulun Zhang (Environmental Science and Pollution Research, 2021)

Dynamics and multi‐annual fate of atmospherically deposited nitrogen in montane tropical forests - Ang Wang; Dexiang Chen; Oliver L. Phillips; Per Gundersen; Xulun Zhou; Geshere A. Gurmesa; Shanlong Li; Weixing Zhu; Erik A. Hobbie; Xueyan Wang; Yunting Fang (Global Change Biology, 2021)
The effects of nitrogen (N) deposition on forests largely depend on its fate after entering the ecosystem. While several studies have addressed the forest fate of N deposition using 15 N tracers, the long‐term fate and redistribution of deposited N in tropical forests remains unknown. Here, we applied 15 N tracers to examine the fates of deposited ammonium ( ) and nitrate ( ) separately over 3 years in a primary and a secondary tropical montane forest in southern China. Three months after 15 N tracer addition, over 60% of 15 N was retained in the forests studied. Total ecosystem retention did not change over the study period, but between 3 months and 3 years following deposition 15 N recovery in plants increased from 10% to 19% and 13% to 22% in the primary and secondary forests, respectively, while 15 N recovery in the organic soil declined from 16% to 2% and 9% to 2%. Mineral soil retained 50% and 35% of 15 N in the primary and secondary forests, with retention being stable over time. The total ecosystem retention of the two N forms did not differ significantly, but plants retained more than and the organic soil more than . Mineral soil did not differ in and retention. Compared to temperate forests, proportionally more 15 N was distributed to mineral soil and plants in these tropical forests. Overall, our results suggest that atmospherically deposited and is rapidly lost in the short term (months) but thereafter securely retained within the ecosystem, with retained N becoming redistributed to plants and mineral soil from the organic soil. This long‐term N retention may benefit tropical montane forest growth and enhance ecosystem carbon sequestration.

Numerical Simulation of a Polar Ship Moving in Level Ice Based on a One-Way Coupling Method - Bao-Yu Ni; Zi-Wang Chen; Kai Zhong; Xin-Ang Li; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2020)
In most previous ice–ship interaction studies involving fluid effects, ice was taken as unbreakable. Building breakable level ice on water domain is still a big challenge in numerical simulation. This paper overcomes this difficulty and presents a numerical modeling of a ship moving in level ice on the water by using a one-way CFD-DEM (computational fluid dynamics-discrete element method) coupling method. The detailed numerical processes and techniques are introduced. The ice crack propagation process including radial and circular cracks have been observed. Numerical results are compared with previous experimental data and good agreement has been achieved. The results show that water resistance is an order of magnitude smaller than ice resistance during the ice-breaking process. Ice resistance shows strong oscillation along with ice failure process, which are affected by ship speed and ice thickness significantly.

Vascular KATP channels protect from cardiac dysfunction and preserve cardiac metabolism during endotoxemia - Qadeer Aziz; Jianmin Chen; Amie J Moyes; Yiwen Li; Naomi A Anderson; Richard Ang; Dunja Aksentijevic; Sonia Sebastian; Adrian J Hobbs; Christoph Thiemermann; Andrew Tinker (Journal of Molecular Medicine, 2020)
K ATP channels in the vasculature composed of Kir6.1 regulate vascular tone and may contribute to the pathogenesis of endotoxemia. We used mice with cell-specific deletion of Kir6.1 in smooth muscle (smKO) and endothelium (eKO) to investigate this question. We found that smKO mice had a significant survival disadvantage compared with their littermate controls when treated with a sub-lethal dose of lipopolysaccharide (LPS). All cohorts of mice became hypotensive following bacterial LPS administration; however, mean arterial pressure in WT mice recovered to normal levels, whereas smKO struggled to overcome LPS-induced hypotension. In vivo and ex vivo investigations revealed pronounced cardiac dysfunction in LPS-treated smKO, but not in eKO mice. Similar results were observed in a cecal slurry injection model. Metabolomic profiling of hearts revealed significantly reduced levels of metabolites involved in redox/energetics, TCA cycle, lipid/fatty acid and amino acid metabolism. Vascular smooth muscle-localised K ATP channels have a critical role in the response to systemic infection by normalising cardiac function and haemodynamics through metabolic homeostasis. Key messages • Mice lacking vascular K ATP channels are more susceptible to death from infection. • Absence of smooth muscle K ATP channels depresses cardiac function during infection. • Cardiac dysfunction is accompanied by profound changes in cellular metabolites. • Findings from this study suggest a protective role for vascular K ATP channels in response to systemic infection.

Spatial Accessibility to Shopping Malls in Nanjing, China: Comparative Analysis with Multiple Transportation Modes - Ang Li; Jie Chen; Tianlu Qian; Wenhan Zhang; Jiechen Wang (Chinese Geographical Science, 2020)

Colletotrichum fructicola STE50 is required for vegetative growth, asexual reproduction, appressorium formation, pathogenicity and the response to external stress - Yan-ying Chen; Jun-ang Liu; Shi-qiang Jiang; He Li; Guo-ying Zhou (Journal of Plant Pathology, 2020)

Correction to: NR2A- and NR2B-NMDA receptors and drebrin within postsynaptic spines of the hippocampus correlate with hunger-evoked exercise - Yi-Wen Chen; Hannah Actor-Engel; Ang Doma Sherpa; Lauren Klingensmith; Tara G. Chowdhury; Chiye Aoki (Brain Structure and Function, 2020)

Effects of Drug Particle Size and Lipid Additives on Drug Release from Paraffin Wax Formulations Prepared by Spray Congealing Technique - Hongyi Ouyang; Chen Yee Ang; Paul Wan Sia Heng; Lai Wah Chan (AAPS PharmSciTech, 2019)

Disruption of bone morphogenetic protein type IA receptor in osteoblasts impairs bone quality and bone strength in mice - Quanwei Bao; Ang Li; Sixu Chen; Jianquan Feng; Huayu Liu; Hao Qin; Junfeng Li; Daocheng Liu; Yue Shen; Zhaowen Zong (Cell and Tissue Research, 2018)

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)

Nitrogen removal performance and microbial community of an enhanced multistage A/O biofilm reactor treating low-strength domestic wastewater - Han Chen; Ang Li; Qiao Wang; Di Cui; Chongwei Cui; Fang Ma (Biodegradation, 2018)

Transverse Isotropy of Phyllite Under Brazilian Tests: Laboratory Testing and Numerical Simulations - Guowen Xu; Chuan He; Ziquan Chen; Ang Su (Rock Mechanics and Rock Engineering, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

A moso bamboo (Phyllostachys edulis) miniature inverted-repeat transposable element (MITE): the possible role of a suppressor - Mingbing Zhou; Ang Chen; Qianqian Zhou; Dingqin Tang; Heikki Hänninen (Tree Genetics & Genomes, 2017)

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

NR2A- and NR2B-NMDA receptors and drebrin within postsynaptic spines of the hippocampus correlate with hunger-evoked exercise - Yi-Wen Chen; Hannah Actor-Engel; Ang Doma Sherpa; Lauren Klingensmith; Tara G. Chowdhury; Chiye Aoki (Brain Structure and Function, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Adsorption behavior of tetracycline by extracellular polymeric substrates extracted from Klebsiella sp. J1 - Ang Li; Shanshan Pi; Wei Wei; Ting Chen; Jixian Yang; Fang Ma (Environmental Science and Pollution Research, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Conservation of reef corals in the South China Sea based on species and evolutionary diversity - Danwei Huang; Bert W. Hoeksema; Yang Amri Affendi; Put O. Ang; Chaolun A. Chen; Hui Huang; David J. W. Lane; Wilfredo Y. Licuanan; Ouk Vibol; Si Tuan Vo; Thamasak Yeemin; Loke Ming Chou (Biodiversity and Conservation, 2016)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Extraordinary diversity of reef corals in the South China Sea - Danwei Huang; Wilfredo Y. Licuanan; Bert W. Hoeksema; Chaolun Allen Chen; Put O. Ang; Hui Huang; David J. W. Lane; Si Tuan Vo; Zarinah Waheed; Yang Amri Affendi; Thamasak Yeemin; Loke Ming Chou (Marine Biodiversity, 2015)

Identification of fucans from four species of sea cucumber by high temperature 1H NMR - Nian Wu; Shiguo Chen; Xingqian Ye; Guoyun Li; Li’ang Yin; Changhu Xue (Journal of Ocean University of China, 2014)

Variations in nitrogen-15 natural abundance of plant and soil systems in four remote tropical rainforests, southern China - Ang Wang; Yun-Ting Fang; De-Xiang Chen; Keisuke Koba; Akiko Makabe; Yi-De Li; Tu-Shou Luo; Muneoki Yoh (Oecologia, 2014)

Dynamic mobilization of PGC-1α mediates mitochondrial biogenesis for the protection of RGC-5 cells by resveratrol during serum deprivation - Shida Chen; Qian Fan; Ang Li; Dongjiang Liao; Jian Ge; Alan M. Laties; Xiulan Zhang (Apoptosis, 2013)

Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717 - Tongwen Zhang; Yujiang Yuan; Wenshou Wei; Shulong Yu; Ruibo Zhang; Huaming Shang; Feng Chen; Zi'ang Fan; Li Qin (International Journal of Climatology, 2013)
In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p

Low-intensity pulsed ultrasound-mediated stimulation of hematopoietic stem/progenitor cell viability, proliferation and differentiation in vitro - Peng Xu; Hilal Gul-Uludag; Woon T. Ang; Xiaoyan Yang; Min Huang; Leah Marquez-Curtis; Locksley McGann; Anna Janowska-Wieczorek; James Xing; Eric Swanson; Jie Chen (Biotechnology Letters, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Environmental significance of RSL in ancient city wall: historical desertification of Ordos Plateau, Northern China - Yinzhou Huang; Nai-ang Wang; Tonghui He; Hongyi Chen; Wenyong Feng; Hao Long (Climatic Change, 2009)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)